Effectiveness of Aromatherapy on Ameliorating Fatigue in Adults: A Meta-Analysis. (13th April 2022) - Wang, Qiuting; Wei, Lin; Luo, Yueming; Lin, Lijun; Deng, Chong; Hu, Ping; Zhu, Lijia; Liu, Yangchen; Lin, Meizhen
Abstract : Background . Fatigue is a common symptom in adults that may cause physical and psychological problems and reduce quality of life. Aromatherapy could possibly provide relief for those suffering from fatigue. Here, we evaluated the effect of aromatherapy on fatigue in adults. Methods . We searched the PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Chinese Biomedical Literature, SinoMed, Wanfang, and Chinese Scientific Journal Database databases for randomized controlled trials of aromatherapy treatment for fatigue in adults from their inception to June 2021. Two reviewers searched independently, extracted the characteristics of the studies, and assessed the risk of bias using the Cochrane risk-of-bias tool and Stata v. 14.0. Results . Nineteen studies were included in this systematic review. Aromatherapy had a significant effect on fatigue (standardized mean difference −0.64, 95% confidence interval−1.14, −0.15, I 2 94.4%, P < 0.001 ). Subgroup analysis according to aromatic type, substance, frequency, treatment duration, intervention, outcomes measurement, and population type showed that aromatherapy had a significantly greater effect in the intervention group, compared to the control group. Funnel plots and Egger's test indicated no significant publication bias. Conclusion . Our results suggest that aromatherapy ameliorates fatigue in adults who suffer from chronic diseases. A rigorous intervention program and larger randomized controlled trials are needed.